1977
DOI: 10.1148/124.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid Tumors—Treatment and Prognosis

Abstract: Desmoid tumors are locally invasive benign tumors arising from musculoaponeurotic structures which are classified as fibromatoses and which have generally high post-surgical recurrence rates. Sixteen patients with desmoid tumors were treated with irradiation and evaluated for 2 to 6 years post-treatment. Of the 16, 13 cases have been controlled without recurrence. Virtually complete resolution of the tumor mass has been accomplished without the disfigurement and dysfunction characteristic of the radical surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

1978
1978
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…One hundred fiftytwo primary tumors were excised with wide or radical microscopic surgical margins, while in 260 cases a marginal or intralesional excision was performed. In the [22] 1992 10 X X Ayadi [55] 2003 12 X X Ayala [23] 1986 25 X X X Ballo [24] 1999 98 X X X Bataini [25] 1988 20 X X Brueckl [26] 2001 12 X X Catton [27] 1995 33 X X Cole [28] 1969 12 X X X Dahn [29] 1963 9 X X Das Gupta [30] 1969 60 X X Easter [6] 1989 12 X X X Gansar [31] 1987 5 X X X Goy [32] 1997 45 X X Gronchi [33] 2003 203 X X Higaki [34] 1995 41 X Kamath [35] 1996 43 X Keus [36] 1986 16 X X Khorsand [37] 1985 11 X X Kouho [38] 1997 16 X X Leibel [39] 1983 17 X Leithner [40] 2000 13 X X Masson [41] 1966 34 X X McKinnon [42] 1989 16 X X Merchant [43] 1999 189 X X Mitchell [44] 1998 21 X X Park [45] 2003 22 X X X Plukker [46] 1995 32 X X X Posner [47] 1989 78 X Reitamo [48] 1983 33 X Serpell [49] 1999 11 X X Sorenesen [50] 2002 50 X X Spear [51] 1998 71 X X Taylor [52] 1987 28 X Wara [56] 1977 16 X Ziarek [53] 1983 4 X X X Zlotecki [54] 2002 55 X X X Total excluded 1402…”
Section: Resultsmentioning
confidence: 99%
“…One hundred fiftytwo primary tumors were excised with wide or radical microscopic surgical margins, while in 260 cases a marginal or intralesional excision was performed. In the [22] 1992 10 X X Ayadi [55] 2003 12 X X Ayala [23] 1986 25 X X X Ballo [24] 1999 98 X X X Bataini [25] 1988 20 X X Brueckl [26] 2001 12 X X Catton [27] 1995 33 X X Cole [28] 1969 12 X X X Dahn [29] 1963 9 X X Das Gupta [30] 1969 60 X X Easter [6] 1989 12 X X X Gansar [31] 1987 5 X X X Goy [32] 1997 45 X X Gronchi [33] 2003 203 X X Higaki [34] 1995 41 X Kamath [35] 1996 43 X Keus [36] 1986 16 X X Khorsand [37] 1985 11 X X Kouho [38] 1997 16 X X Leibel [39] 1983 17 X Leithner [40] 2000 13 X X Masson [41] 1966 34 X X McKinnon [42] 1989 16 X X Merchant [43] 1999 189 X X Mitchell [44] 1998 21 X X Park [45] 2003 22 X X X Plukker [46] 1995 32 X X X Posner [47] 1989 78 X Reitamo [48] 1983 33 X Serpell [49] 1999 11 X X Sorenesen [50] 2002 50 X X Spear [51] 1998 71 X X Taylor [52] 1987 28 X Wara [56] 1977 16 X Ziarek [53] 1983 4 X X X Zlotecki [54] 2002 55 X X X Total excluded 1402…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6] Recent molecular studies based on X-chromosome inactivation have identified desmoid tumors to be clonal and thus proved their neoplastic origin. 6 Furthermore, certain molecular abnormalities frequently seen in malignant fibrosarcomas are almost never present in desmoid tumors and are therefore helpful in distinguishing them from their malignant fibroblastic counterparts.…”
mentioning
confidence: 99%
“…Although metastases do not occur, musculoaponeurotic fibromatosis is locally aggressive with a recurrence rate of 25%-77% after surgical excision [11]. Amputation of a limb may be necessary for relief of intractable pain or neurovascular compromise, and death has resulted from infiltration of vital organs [7,11,16]. There is also substantial morbidity related to repeated attempts at surgical resection when primary excision fails to achieve a cure.…”
mentioning
confidence: 99%